Kontribusi Inovasi Bisnis dalam Meningkatkan Repeat Order di Rumah Makan & Warkop OJF Khas Melayu Padang di Kota Medan - Dimas Saragih; Febry Tarigan; Kezia Simbolon; Yosi Simbolon; Dionisius Sihombing; Fadli Agus Triansyah (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze the forms of innovation implemented by Rumah Makan and Warkop OJF Khas Melayu Padang in Medan City and their impact on customer satisfaction and repeat purchases. A case study approach was employed using semi-structured interviews, field observations, and document analysis. Data were analyzed qualitatively using inductive and deductive coding techniques. The findings reveal that innovations encompass product, service, and process aspects. Product innovations include the development of new menu variations, value meal packages, and frozen rendang as souvenirs. Service innovations are reflected in online ordering systems, faster service, loyalty promotions, and a more comfortable dining atmosphere. Process innovations involve centralized kitchen management, efficient ingredient storage, and the use of eco-friendly packaging. Customers generally respond positively, appreciating menu variety, digital convenience, and environmental awareness while maintaining the restaurant’s authentic taste. Innovation has proven to enhance repeat purchases through consistent product quality, friendly service, and loyalty programs. Despite challenges such as limited capital, human resource readiness, and competition, digital service innovation combined with menu development is considered most effective in improving customer satisfaction and loyalty in MSME-based culinary businesses.